Human sporotrichosis: recommendations from the Brazilian Society of Dermatology for the clinical, diagnostic and therapeutic management - Rosane Orofino-Costa; Dayvison Francis Saraiva Freitas; Andréa Reis Bernardes-Engemann; Anderson Messias Rodrigues; Carolina Talhari; Claudia Elise Ferraz; John Verrinder Veasey; Leonardo Quintella; Maria Silvia Laborne Alves de Sousa; Rodrigo Vettorato; Rodrigo de Almeida-Paes; Priscila Marques de Macedo (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: The increase in the zoonotic epidemic of sporotrichosis caused by Sporothrix brasiliensis, which started in the late 1990s in Rio de Janeiro and is now found in almost all Brazilian states, has been equally advancing in neighboring countries of Brazil. Changes in the clinical-epidemiological profile, advances in the laboratory diagnosis of the disease, and therapeutic difficulties have been observed throughout these almost 25 years of the epidemic, although there is no national consensus. The last international guideline dates from 2007. Objectives: Update the clinical classification, diagnostic methods and recommendations on the therapeutic management of patients with sporotrichosis. Methods: Twelve experts in human sporotrichosis were selected from different Brazilian regions, and divided into three work groups: clinical, diagnosis and treatment. The bibliographic research was carried out on the EBSCOHost platform. Meetings took place via electronic mail and remote/face-to-face and hybrid settings, resulting in a questionnaire which pointed out 13 divergences, resolved based on the opinion of the majority of the participants. Results: The clinical classification and laboratory diagnosis were updated. Therapeutic recommendations were made for the different clinical forms. Conclusions: Publication of the first national recommendation, carried out by the Brazilian Society of Dermatology, aimed at the Brazilian scientific community, especially dermatologists, infectologists, pediatricians, family medicine personnel, and laboratory professionals who work in the management of human sporotrichosis.